The Cost of Early Diagnosis of Cognitive Decline in German Memory Clinics - Onurl, Oezguer A.; Wolff-Menzler, Claus; Von Arnim, Christine A. F.; Jessen, Frank; Fink, Gereon R.; Wiltfang, Jens; Laske, Christoph; Schneider, Anja; Levinl, Johannes; Oberstein, Timo; Kornhuber, Johannes; Oberhauser, Felix; et al. (Fortschritte der Neurologie - Psychiatrie, 2022)
Dementias are expensive diseases: the net annual cost in European healthcare is about euro 28.000 per case with a strong stage dependency, of which medical care accounts for about 19%. Diagnostic costs, on the other hand, account for only a small proportion of the total costs. With changes in the guidelines, biomarker tests are becoming increasingly important. At present, the concrete economic impact of biomarker-based diagnosis is largely unknown. To determine the actual costs of diagnostic procedures based on guidelines, we conducted a survey among the members of the German Memory Clinic Network (DNG). From 15 expert centres, the staff engagement time for all procedures was collected. Based on the individual engagement times of the different professions, the total of personnel costs for diagnostics was calculated using current gross personnel costs. The total sum of diagnostic costs (personnel plus procedures) was calculated for three different scenarios e. g. euro 633,97 for diagnostics without biomarkers, euro 1.214,90 for diagnostics with CSF biomarkers and euro 4.740,58 euro for diagnostics with FDG- plus Amyloid-PET. In addition, the actual diagnostic costs of the current practice in expert memory clinics were estimated, taking into account personnel costs, costs for the different procedures and the frequency of their use across all patients. This results in total average costs of euro 1.394,43 per case as the mean across all centres (personnel costs euro 351,72, costs for diagnostic procedures euro 1.042,71). The results show that state-of-the-art diagnosis of dementia and pre-dementia states, such as mild cognitive impairment (MCI) requires financial resources, which are currently not fully reimbursed in Germany. The need for a biomarker-based etiological diagnosis of dementia and pre-dementia states will increase, due to availability of disease-modifying treatments. Therefore, the current gap of reimbursement must be filled by new models of compensation.
CRIS-Team WoS Importer:2022-07-29